Gymnopilus dunensis, a new species from Punjab province, Pakistan - Bashir, Hira; Jabeen, Sana; Bashir, Humaira; Khalid, Abdul Nasir (Phytotaxa, 2020)
Gymnopilus dunensis is described as a new species from Punjab province Pakistan, based on internal transcribed spacer (ITS) sequence data and morphological characters. Presence of grey scales on the pileus, slightly radicating and fibrillose stipe that is white at the apex and orange-brown at the base, and its unique phylogenetic position confirm that this is a new species. It is also different to other species of Gymnopilus because it is found in a semi-arid desert environment.